Go global or go home: comparing the regional vs. global engagement of Brazil and South Africa at the UN General Assembly - Mesquita, R.; Seabra, P. (Politikon, 2020)
Brazil and South Africa have long been regarded as archetypical regional powers, commanding more resources than their neighbours, spearheading regional projects and pursuing high-profile global status. Yet, recent years have also evidenced how the engagement with their regions and acceptance as leading players is often ambiguous and incomplete. How does one ascertain that a regional power privileges either the regional or the global stage? Through an original dataset of Brazilian and South African output at the UN General Assembly between 1994 and 2013, we monitor sponsorship patterns and thematic preferences in order to verify whether these countries indulged their regional partners and topics. Our findings suggest that Brazil and South Africa favoured their immediate neighbourhoods but have gradually engaged their regions in different ways: while Brazilian emphasis on regional peers and themes declined over the years, South Africa developed an increasingly more regionalised UNGA agenda.